Identification and characterization of pathogens causing diseases on Begonia at Eka Karya Bali Botanic Garden - Serdani, Army Dita; Sandy, Yohana Avelia; Li’aini, Arrohmatus Syafaqoh (Kultivasi, 2023)
Begonia is one of the world's largest genera of flowering plants that spread in various tropical and subtropical regions worldwide. However, deforestation, overexploitation, climate change, and pathogen-causing diseases have threatened the diversity of begonia. Diseases on begonia need to be handled seriously because the level of spread and damage can result in the death of the plant. Thus, this study was conducted to identify the main pathogens causing diseases in the begonia which is expected to be basic information in determining the effective control treatment. As a result, begonia collections of Eka Karya Bali Botanic Garden were mainly infected by three pathogenic fungi (Fusarium spp., Oidium begoniae, and Botrytis cinerea) and one bacterium (Xanthomonas begoniae).